Penguatan Kecerdasan Emosioanal Siswa Melalui Strategi Pembelajaran PAI di SMK Islam Ulul Albab Ngronggot - Dayu Feri Apriliansah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Emotional intelligence is one of the 3 human intelligences, emotional intelligence is how humans can control, manage and control feelings so that they can have awareness in behaving and socializing with their environment, teachers' strategies in the learning process that are not appropriate can cause students to be inactive and focused in learning, students are less enthusiastic and some students are noisy in class. The aim of this research is to find out how to strengthen the emotional intelligence of Ulul Albab Ngronggot Islamic Vocational School students and to find out how PAI teachers' strategies are in strengthening emotional intelligence. The research method used is descriptive qualitative analysis which discusses teacher strategies in strengthening students' emotional intelligence. The results of this research are teachers' strategies for strengthening students' emotional intelligence. First, learning includes interactive, interesting, challenging, motivational activities. Second, students' emotional intelligence includes self-awareness, self-control, motivation, empathy and social skills, namely being able to interact well.